PEMIKIRAN MANAJEMEN OEI LIANG LEE DALAM PERSPEKTIF ISLAM: bahasa indonesia - Hikmatul Hidayah (Institut Agama Islam Hidayatullah Batam, 2022)
Management has basically existed since man existed, because in the bottom of man in his daily life will not be separated from the principles of management either directly or indirectly, whether realized or unconsciously. Along with the development of the management era, management science has also developed. Many figures discuss and study management to be developed and applied in segal aspects of human life to achieve the best results. One of the thinkers in this field of management is Oie Liang Lee. What is the concept of management according to him and what are the functions of management according to Oie Liang Lee and how the concept of management thinking Oie Liang Lee is viewed from an Islamic perspective, this is the focus of the purpose of this study. namely analyzing Oie Liang Lee's concept of management thinking and its conformity to the concept of Islam. The writingn of this scientific paper was written using a literature study or library research by examining the thoughts of Oie Liang Lee's Management in his time. In writing this scientific work the author found that according to Oie Liang Lee management is the art and science of planning, organizing, compiling, directing and supervising resources to achieve the goals already set. According to him, the management functions are Planning, Organizing, Directing, Coordinating and Controlling. Viewed from an Islamic perspective, there is a compatibility between Oie Liang Lee's management concept and the values contained in the Qur'an and Hadith.